Restorative Justice: A New Paradigm for Criminal Justice Policy - Schmid, Donald J (Victoria University of Wellington Law Review, 2003)
In this article, Donald Schmid reviews trends towards restorative justice across several common law jurisdictions, most notably New Zealand and the United States. He examines different models of restorative justice and concludes that, while none of these practices will completely eliminate the need for other, court-based criminal justice processes, they have a large number of practical and social advantages over more traditional approaches.